Strategi AS yang Gagal dalam Pembangunan Negara Irak Setelah Jatuhnya Saddam Hussein - Dianata Panji Prasugi; Anak Agung Banyu Perwita; Agung Risdhianto (Departement of Mathematics Education, 2024)
The turbulences occurred in Iraq from the fall of Saddam Hussein in 2003 to present days are proof that the U.S. has never had a workable grand strategy for Iraq or any consistent plans and actions to support the national building phase after the war. The U.S. seemed to be focus more on thinking tactically, rather than strategically where at the same time underestimating Iraq’s strategic importance in the region. This paper attempts to point out the failure of the U.S. in the national-building process in Iraq from the perspective of ethnic, political religion and terrorism in contemporary international relations, and what could have been done differently during the civil war and the humanitarian intervention. The article research method was conducted using document-based qualitative through various sources, including books, journals, and news on the internet. The research results of this article indicate that the U.S. failed to understand three aspects that set the tone in the middle east: ethnic, political religion, and terrorism.